On velocity and heat transfer of MHD forced convective boundary layer flow over a sphere - Mohammad, Nurul Farahain; Lim, Yeou Jiann; Wan Abdullah, Wan Rukaida; Ismail, Zuhaila (Penerbit UTM Press, 2018)
The motion of the fluid past a body is of great interest for academic research due to its various practical applications. This kind of fluid flow is known as a boundary layer flow. Various topics in boundary layer flow and heat transfer are presented in this book. These include the unsteady case, magnetohydrodynamics case, two phase flow, nanofluids and Jeffery fluid. The authors discussed the mathematical solutions which were obtained whether using the exact solution such as Keller-Box method and Runge Kutta Fehlberg fourth-fifth order method (RKF45 method). This book can be a reference for the future researchers especially in fluid mechanics field.